Conditioned inhibition of emotional responses: retardation and summation with cues for IAPS outcomes - Thurston, Meghan Dory; Cassaday, Helen J. (Elsevier, 2015)
Conditioned inhibition occurs when a stimulus inhibits the responses that would normally occur to a conditioned stimulus that previously predicted an outcome of interest (the unconditioned stimulus, which elicits responding unconditionally). The present study tested inhibitory learning using emotionally salient cues provided by the use of pictures from the International Affective Picture System (IAPS). The procedure in use was adapted to confirm the demonstration of conditioned inhibition using two key transfer tests, retardation and summation. Experiment 1 showed the development of the predicted discrimination learning for negative outcomes but not for positive outcomes. Experiment 2 found evidence for retardation. Furthermore, this reduced learning was clearly related to the conditioned emotional response to the US images; individuals rated transfer images as positive if they had previously signalled the absence of a negative outcome. Experiment 3 showed that the conditioned inhibition was confirmed by summation test. Thus, inhibitory learning was confirmed by both retardation and summation tests, which between them control for alternative explanations of apparent conditioned inhibition, conducted on different participants but using the same discrimination learning procedure. Moreover, the use of emotionally salient cues as the unconditioned stimuli more closely resembles the traditional Pavlovian paradigm.